Preliminary Techno-Economic Feasibility of Biodegradable Food Packaging from Luffa Acutangula Peel in Indonesia - Jasmine Rahma Kesuma Nirvana; Shafwan Amrullah; M. Farras Abiyyuddin (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2025)
In recent years, microplastics and nanoplastics have become current challenges due to advancing food safety. Food packaging is one of the materials used in society by food enterprises; meanwhile, the growth rate of citizens is increasing, and the demand for ready-to-eat food may be a considerable issue for producing eco-friendly, biodegradable food packaging. Basically, biodegradable food packaging is developed from natural resources such as agricultural waste. Luffa acutangular fruit is a commodity produced in Asia, including Indonesia. The purpose of this study was to analyze the techno-economic feasibility of biodegradable food packaging from Luffa acutangula fruit peel from engineering, sustainability, and economic perspectives. The method used in this study was to integrate engineering and economic evaluation to assess the feasibility of biodegradable food packaging from Luffa acutangula fruit peel at an industrial scale, to develop a broader, environmentally friendly product manufactured in Indonesia. From an engineering and sustainability perspective, we addressed the technical challenges of food packaging and also demonstrated future sustainability considerations for the circular economy in Indonesia. Besides, from an economic perspective, we analyzed the food packaging's economic feasibility to assess its profitability. Economic feasibility: Return on Investment (ROI) after tax is 94,42%; Payback Period (PBP) after tax is about 1,18 years; Break-Even Point (BEP) is about 52,09%. The BEP value for the chemical plant was in the 40%-60% range. It can support Indonesia's circular economy by reducing agricultural waste, especially fruit waste. For future research recommendations, the study should not rely solely on preliminary techno-economic feasibility assessment results but also on policy implications, life-cycle assessment, and ongoing cost-benefit analysis.